One century of the discovery of arsenicosis in Latin America (1914-2014) As 2014 proceedings of the 5th International Congress on Arsenic in the Environment, May 11-16, 2014, Buenos Aires, Argentina - Litter, Marta I.; Nicolli, Hugo B.; Meichtry, Martin; Quici, Natalia; Bundschuh, Jochen; Bhattacharya, Prosun; Naidu, R. (Arsenic in the environment. Proceedings., 2014)
The Congress ""Arsenic in the Environment"" offers an international, multi- and interdisciplinary discussion platform for research aimed towards a holistic solution to the problem posed by the environmental toxin arsenic, with considerable societal impact. The congress has focused on cutting edge and breakthrough research in physical, chemical, toxicological, medical, agricultural and other specific issues on arsenic across a broader environmental realm. The Congress "Arsenic in the Environment" was first organized in Mexico City (As2006) followed by As2008 in Valencia, Spain, As2010 in Tai.